“We can return to Normal”: Tourism, Poverty, and Development Economic of Bali in Indonesia - Dewi, Made Heny Urmila; Narmaditya, Bagus Shandy; Irwansyah, M. Rudi (Journal of Ecohumanism, 2024)
Tourism is the sector most impacted during the pandemic, while the effort to make tourism go back to normal post-pandemic will promote economic development. Therefore, this study aims to investigate the strategies for the tourism sector to return to normal as the abundance for Bali in Indonesia. To deal with, this study involved 120 participants in some areas in Bali that were further analyzed using SWOT analysis. The findings indicate that the decline in the tourism sector due to the pandemic has caused Bali’s economic performance to diminish dramatically, which causes the issue of poverty. For this reason, the results suggest that the tourism recovery strategy must start with efforts to recover in the post-pandemic, including accelerating traditional village-based community enhancement and dealing with disaster mitigation, which helps speed up the handling of the pandemic in Bali Province. Lastly, the digital promotion for tourism can raise the visitors to revisit Bali as the main priority for tourism. Thus, the findings can be used by policy scholars and the government to make the economy normal.